Effect of Product Partition on the Synthesis of Butyl-Β-D-Galactoside from Aspergillus Oryzae - Arenas-Salinas, F; Vera-Vera, C; Muñoz-Becerra, K; Muñoz-Becerra, K; Ahumada-Muñoz , D (Elsevier Ltd, 2021)
The effect of donor substrate and products partitioning on the performance of butyl-β-galactoside synthesis with Aspergillus oryzae β-galactosidase was studied. Firstly, the partition coefficient of the donor substrate (lactose) and the reaction products (glucose, galactose and butyl-β-galactoside) were determined in the aqueous and organic phases of the reaction medium. In the temperature range studied (30 to 50 °C), butyl β-galactoside was roughly 130 and 30-fold more soluble in the organic phase than lactose and the monosaccharides, respectively. Afterward, the effect of the 1-butanol/ aqueous phase ratio (α) on the reaction was evaluated in the range from 0.25 to 4. Results show that higher values of α reduce the incidence of secondary hydrolysis by favoring the extraction of butyl-β-galactoside into the organic phase where it is not hydrolyzed, leading to higher yields. Also, major interfacial properties for butyl-β-galactoside were determined at 25 °C. © 2021 Elsevier Ltd
Keywords: Alkyl-glycoside; Lactose; beta-galactosidase; Butyl-beta-galactoside